Growth and survival of Indan Whiteshrimp, Peneus indicus, Larvae Fed with different diets. - Arbizo, Jeric (Iloilo City UPHSI, 2008)
Asia continues to lead in global shrimp production with about 86% of the total production in 2003. A surge in pacific white shrimp production particularly in China and Thailand challenged the black tiger dominance in Asia (Mexican, 2004). In the Philippines, the importation of the exotic Penaeus vannamei was banned until the early part last year. SEAFDEC-AQD is promoting the culture of the local white shrimp Penaeus indicus (locally known as hipong puti) as a viable option to P. vannamei. P. indicus is an important commercial penaeid shrimp species cultured mainly on extensive farms in Southeast Asia (Kumlu & Jones, 1995). Hatchery techniques for P. indicus are not yet well established although this wite shrimp species was a priority species for research in SEAFDEC (Parado-Estepa, 1995). Successful larval rearing of P. monodon, P. japonicus, P. vannamei, and P. stylirostis was achieved using live conventional diets (live microalgae and Artermia), however, there are numerous attempts to partially or completely replace natural diets with various artificial diets (Kumlu & Jones, 1995). Therefore, studies to partially replace natural diets with the use of commercial or artificial food for larval rearing should be carried out. This study was done to compare the growth and survival of larvae on natural food (microalgae) alone and in combination with commercial feeds and hard boiled chicken egg yolk.
Research II : Research Manuscripts
Keywords: Indian Whiteshrimps